IMPLEMENTATION OF EDUCATIONAL NATIONAL STANDARD POLICY ON THE OPERATION OF BASIC EDUCATION (Case Study in Wajo District, South Sulawesi) - Sitti Aminah; Imran Ismail (Universitas Sebelas Maret, 2018)
The background study of this research is to develop national education standards of the basic education. In this research study, the researcher tries to see and analyze the prevailing condition schools in the field of education. The goals of this research knowledge of the implementation of the National Education Standards policy and the determinant factors can support the implementation of National Education Standards policy on the implementation of National Standard School in Wajo Regency. The design of this research was descriptive qualitative research. The data for this research was collected through observation, interview, and documentation. The resulting analysis can be concluded as follows: First, the stages of implementation of the National Standard Primary School policy have not been implemented optimally because of overlapping. Second, the determinant factors that influence the implementation of the National Standard Primary School policy include resource support is still very limited, and third, less motivated elementary schools to get involved in the implementation of the National Standard Primary School policy, especially elementary schools in the standard category. In suggestion, good cooperation is needed with all parties and stakeholders in the implementation of the National Standard Primary School program through efforts to obtain common views and responsibilities towards Primary School development